Impact of Corporate Social Responsibility in the organizational climate [Impacto de la responsabilidad social empresarial en el clima organizacional] (2018)
The article presents the impact of social action in the internal processes of organizations. A model of structured equations applied to the companies of Grupo Empresarial Antioqueño is used for research. Concluding that there are positive impacts on administrative processes resulting from social investment. © 2018.